1995
DOI: 10.1029/95jb00148
|View full text |Cite
|
Sign up to set email alerts
|

Deflection of paleomagnetic directions due to magnetization of the underlying terrain

Abstract: In the summers of 1989 and 1991 we made 344 near‐ground level measurements of the ambient geomagnetic field above recent basalts on the island of Hawaii using a three‐component fluxgate magnetometer. We studied 12 surface features, including a lava pond, lava channels, long tilted blocks, smooth sloping surfaces, two fissures, and a deep U‐shaped road cut. We observed substantial differences (up to 20°) between the observed and expected (International Geomagnetic Reference Field, IGRF) magnetic field direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 43 publications
3
63
2
Order By: Relevance
“…So-called local anomalies due to terrain effects (e.g. Baag et al, 1995;Valet and Soler, 1999) in our data would therefore not be averaged out as good as in Böhnel et al (1982) and Schnepp (1996)'s data. However, as Böhnel et al (1982) and Schnepp (1996)'s palaeodirections generally showed low scatter (α 95 usually less than 4°), it appears unlikely that these large deviations would be due to the sampling method.…”
Section: Palaeomagnetic Directionsmentioning
confidence: 81%
“…So-called local anomalies due to terrain effects (e.g. Baag et al, 1995;Valet and Soler, 1999) in our data would therefore not be averaged out as good as in Böhnel et al (1982) and Schnepp (1996)'s data. However, as Böhnel et al (1982) and Schnepp (1996)'s palaeodirections generally showed low scatter (α 95 usually less than 4°), it appears unlikely that these large deviations would be due to the sampling method.…”
Section: Palaeomagnetic Directionsmentioning
confidence: 81%
“…two sites (e.g., Castro and Brown, 1987;Baag et al, 1995;Urrutia-Fucugauchi et al, 2004). Small movements of the outcrop could also be the cause of the error.…”
Section: Fukkoshi Lavas Of ∼100 Kamentioning
confidence: 99%
“…Furthermore, this explains why the k-values associated with the directions may be rather low for volcanic products: by sampling the cooling unit over large distances, small post-cooling movements within the outcrop or of the underlying terrain are averaged, lowering the k-values, but increasing the reliability of the directions. Moreover, potential local anomalies in the field (Baag et al 1995;Valet & Soler 1999) are suppressed by this sampling strategy.…”
Section: Palaeodirectionsmentioning
confidence: 99%